A Cost-Effective Digital Solution for Community Libraries: A TAM Evaluation of a CMS-Based Book Circulation System - Vina Zahrotun Kamila; Eko Subastian; Putut Pamilih Widagdo; Riftika Rizawanti (Malikussaleh University, Aceh, Indonesia, 2025)
The digital transformation of community-based libraries in developing regions requires careful consideration of user acceptance factors for successful implementation, particularly when managing physical book collections through online systems. This study evaluates user acceptance of a CMS-based online book circulation system implemented in